2014
DOI: 10.1111/cmi.12359
|View full text |Cite
|
Sign up to set email alerts
|

Organization and function of an actin cytoskeleton inPlasmodium falciparumgametocytes

Abstract: SummaryIn preparation for transmission to its mosquito vector, Plasmodium falciparum, the most virulent of the human malaria parasites, adopts an unusual elongated shape. Here we describe a previously unrecognized actin-based cytoskeleton that is assembled in maturing P. falciparum gametocytes. Differential extraction reveals the presence of a highly stabilized population of F-actin at all stages of development. Super-resolution microscopy reveals an F-actin cytoskeleton that is concentrated at the ends of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
58
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 82 publications
5
58
0
Order By: Relevance
“…It is known that gametocytes possess a trilaminar membrane structure subtended by a layer of structural microtubules that is reminiscent of that of invasive and motile stages (Angrisano et al., 2012, Sinden et al., 1978). It is also known that an F-actin cytoskeleton is concentrated at the ends of the elongating gametocyte, which extends inward along the microtubule cytoskeleton, and is still present in stage V gametocytes (Hliscs et al., 2015). Actin I is the major and ubiquitously expressed actin and is present in both male and female sexual stages, while actin II, a second conventional actin, is specifically expressed by the sexual stages (Deligianni et al., 2011, Rupp et al., 2011, Wesseling et al., 1989).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that gametocytes possess a trilaminar membrane structure subtended by a layer of structural microtubules that is reminiscent of that of invasive and motile stages (Angrisano et al., 2012, Sinden et al., 1978). It is also known that an F-actin cytoskeleton is concentrated at the ends of the elongating gametocyte, which extends inward along the microtubule cytoskeleton, and is still present in stage V gametocytes (Hliscs et al., 2015). Actin I is the major and ubiquitously expressed actin and is present in both male and female sexual stages, while actin II, a second conventional actin, is specifically expressed by the sexual stages (Deligianni et al., 2011, Rupp et al., 2011, Wesseling et al., 1989).…”
Section: Discussionmentioning
confidence: 99%
“…S5A). It is important to note that these effects do not appear to result from compromised parasite viability, because we have previously shown that short-term cytochalasin treatment does not prevent gametocyte maturation (20).…”
Section: Chemical Modulation Of the Membrane Skeleton Enhancesmentioning
confidence: 97%
“…This raises concerns about previous studies of actin polymerization kinetics based on mis-folded actin. Furthermore, imaging studies on different life cycle stages of the apicomplexan parasite, Plasmodium falciparum, demonstrated the formation of an extensive F-actin cytoskeleton in both gametocytes and ookinetes (Hliscs et al, 2015; Siden-Kiamos et al, 2012). Using 3D-SIM it was demonstrated in gametocytes that these filaments appear to be organized in the cytoplasm, below the Inner Membrane Complex (IMC; a specialised structure found in apicomplexans that consists of membranous vesicles and structural components located just beneath the plasma membrane) of the parasite rather than between the IMC and the plasma membrane (Hliscs et al, 2015), where it is thought to power parasite gliding motility (Meissner et al, 2013).…”
Section: Introductionmentioning
confidence: 99%